# Factor theorem

Announcements
#1
Show that (x-p) is a factor of (x-q)^7+(q-p)^7.

I have put x=p to get f(p)=(p-q)^7. Then (p-q)(p-q)^6. I do not know how to continue.

I have also tried putting x=q to get (q-p)(q-p)^6. Thanks in advance for any pointers.
0
#2
Show that x-p is a factor of (x-q)^7+(q-p)^7.

I have put x=p to get f(p)=(p-q)^7=(p-q)(p-q)^6 but then I do not know how to continue.

I have also tried x=q to get (q--p)^7=(q-p)(q-p)^6. Thanks in advance for any pointers.
0
3 years ago
#3
(Original post by chatterclaw73)
Show that x-p is a factor of (x-q)^7+(q-p)^7.

I have put x=p to get f(p)=(p-q)^7=(p-q)(p-q)^6 but then I do not know how to continue.

I have also tried x=q to get (q--p)^7=(q-p)(q-p)^6. Thanks in advance for any pointers. is a factor if, and only if, is a solution to .

So, if you put in into the function, you get: Can you show that this is indeed zero?
0
#4
Thanks!
0
X

new posts Back
to top
Latest

### Oops, nobody has postedin the last few hours.

Why not re-start the conversation?

see more

### Poll

Join the discussion

They're better than I expected (20)
31.75%
They're what I expected (19)
30.16%
They're worse than what I expected (24)
38.1%